PENERAPAN MODEL PEMBELAJARAN OPEN ENDED PROBLEM DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIPA 5 SMA NEGERI 2 DENPASAR DENGAN PEMBELAJARAN DARING - Ni Komang Wirasti (Widyadari : Jurnal Pendidikan, 2021)
Online learning is learning that is done online, using learning applications and social networks. Open-ended problems are learning that begins with giving problems openly with various solutions and solutions. The purpose of this study was to determine the responses and results of students' mathematics learning through the application of an open ended problem learning model with online learning using the zoom application and google classroom. This type of research is classroom action research which consists of 4 stages, namely: planning, implementing actions, observing and reflecting which is carried out in 2 cycles. The research subjects were students of class XI MIPA 5 SMA Negeri 2 Denpasar in the academic year 2020/2021 as many as 46 students. Based on the results of the analysis, it can be concluded (1) the application of the open-ended problem learning model with online learning can improve students' mathematics learning outcomes, (2) there is a positive response from class XI IPA 5 students at SMA Negeri 2 Denpasar towards the application of the open-ended problem learning model with online learning in mathematics lessons on matrix material